2007
DOI: 10.1093/rheumatology/kel326
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation of the anti-TNF-  agents in patients with rheumatoid arthritis. A systematic review

Abstract: Dose escalation is common in patients treated with infliximab, and less frequent with etanercept. In a proportion of patients, the dose escalation seems effective. The design and evidence level of the available studies limit the strength of the conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 8 publications
3
33
0
5
Order By: Relevance
“…on ADA or IFX in situations of suboptimal treatment response but not for patients on ETN. [18][19][20][44][45][46][47] Dose escalation patterns obtained in the present study were similar to those reported across a number of dose escalation studies with the proportion of patients having a dose escalation being consistently and significantly lower for ETN compared with ADA and IFX. 28,29,34,35,37,39,40,42,48 Across all methods used to define dose escalation, the proportions ranged from 0.4% to 10.3%, 8.3% to 33.6%, and 16.4% to 60% for ETN, ADA, and IFX, respectively.…”
Section: Limitationssupporting
confidence: 78%
“…on ADA or IFX in situations of suboptimal treatment response but not for patients on ETN. [18][19][20][44][45][46][47] Dose escalation patterns obtained in the present study were similar to those reported across a number of dose escalation studies with the proportion of patients having a dose escalation being consistently and significantly lower for ETN compared with ADA and IFX. 28,29,34,35,37,39,40,42,48 Across all methods used to define dose escalation, the proportions ranged from 0.4% to 10.3%, 8.3% to 33.6%, and 16.4% to 60% for ETN, ADA, and IFX, respectively.…”
Section: Limitationssupporting
confidence: 78%
“…In any case, any savings from vial sharing are dwarfed by dose escalation. 176 In the cited systematic review, 44% of patients treated with IFX had the drug dose increased.…”
Section: Estimates Of Costsmentioning
confidence: 99%
“…For ABT there was a further HAQ reduction on treatment based on an analysis of ATTAIN and an extension of RTX trials 130,176 (-0.0729 and -0.013, respectively). For all other treatments (biologic drugs and conventional DMARDs) an annual increase in HAQ score of 0.012 was assumed based on an ERG STA report on RTX (calculation was actually based on nonbiologic data).…”
Section: Estimates Of Clinical Effectiveness -Long Termmentioning
confidence: 99%
“…For example, an analysis of RA patients in the US showed that dose frequency was increased in ϳ40% of patients receiving infliximab (16). Dose escalation of TNF inhibitors is also relatively common internationally (17). It is unclear as to why some physicians might choose to escalate the dose of TNF inhibitors despite limited evidence to support this practice.…”
Section: Discussionmentioning
confidence: 99%